CASE STUDY SURABAYA RELIGIOUS COURT JUDGEMENT ABOUT GRANDCHILDREN AS SUBSTITUTE HEIRS WHO CONTROL INHERITANCE JUDGING FROM ISLAMIC LAW - Wulansari, Esti Putri; Supriyatni, Renny; Kusmayanti, Hazar (Fakultas Hukum Universitas Padjadjaran, 2023)
Inheritance is an important part of one legal event, namely death. The legal consequences that arise are the management and continuation of the rights and obligations of someone who has died. This paper examines the juridical aspect of inheritance distribution to grandchildren as substitute heirs who control the inheritance. The research method used is a normative juridical approach with analytical descriptive specifications. The purpose of this study is to determine the position of the substitute heir who controls the inheritance in obtaining a share of the inheritance. Grandchildren as substitute heirs according to Islamic Law are not entitled to control and obtain inheritance. However, in KHI, grandchildren as heirs have the right to inherit no more than the other heirs, which is only 1/3 of the share.